ADAPTASI BANGUNAN FALA KANCI DI TERNATE DALAM UPAYA PENGURANGAN RISIKO BENCANA - Ibrahim, Maulana (Journal of Science and Engineering, 2025)
Disaster risk reduction is an effort that can be made by various parties to reduce the negative impacts that occur when a disaster occurs. This can be done in various facilities and infrastructure both in cities and villages, including in housing or residential homes.This study aims to evaluate the resilience of Fala Kanci buildings in Ternate with an assessment method based on standards issued by the government and analyzed with building resilience standards according to the type of construction, material, design and function of the building.The Fala Kanci studied were those that had been processed and reused not only as housing or had been utilized as buildings with mixed functions between housing and commercial or social functions.